2008
DOI: 10.1016/j.actpsy.2008.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel coordination stability: Integrated goal representations in simultaneous intra-personal and inter-agent coordination

Abstract: The influence of integrated goal representations on multilevel coordination stability was investigated in a task that required finger tapping in antiphase with metronomic tone sequences (inter-agent coordination) while alternating between the two hands (intra-personal coordination). The maximum rate at which musicians could perform this task was measured when taps did or did not trigger feedback tones. Tones produced by the two hands (very low, low, medium, high, very high) could be the same as, or different f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…Furthermore, bimanual coordination is often required in conjunction with the coordination to an external cue like a metronome or a target line. This hand-stimulus coupling (Keller & Repp, 2008) has been described to be weaker than hand-hand coupling, that is the mutual interaction between the hands (Byblow, Chua, & Goodman, 1995;Chua & Weeks, 1997;Schmidt, Bienvenu, Fitzpatrick, & Amazeen, 1998). In addition, it has been shown that providing haptic contact at reversal points reinforces finger-stimulus coupling and can thereby stabilize bimanual coordination (e.g., Calvin, Milliex, Coyle, & Temprado, 2004).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, bimanual coordination is often required in conjunction with the coordination to an external cue like a metronome or a target line. This hand-stimulus coupling (Keller & Repp, 2008) has been described to be weaker than hand-hand coupling, that is the mutual interaction between the hands (Byblow, Chua, & Goodman, 1995;Chua & Weeks, 1997;Schmidt, Bienvenu, Fitzpatrick, & Amazeen, 1998). In addition, it has been shown that providing haptic contact at reversal points reinforces finger-stimulus coupling and can thereby stabilize bimanual coordination (e.g., Calvin, Milliex, Coyle, & Temprado, 2004).…”
mentioning
confidence: 95%
“…In addition, Wishart, Lee, Cunningham, and Murdoch (2002) showed that, when compared to terminal visual feedback, concurrent visual feedback led to better learning of a new coordination pattern, although attention needs to be divided between the handhand and hand-stimulus couplings to cope with the stimulus (Keller & Repp, 2008). Older adults learned the task within three days, but they did not reach younger adults' performance levels, who learned the task within one day .…”
mentioning
confidence: 97%
“…In either case, the task may be to synchronize taps with all sequences simultaneously or to single out a target sequence and regard the other sequences as distractors. Keller and Repp (2008) investigated the effect of melodic pitch feedback on performance of a difficult SMS task. Musicians were required to tap in antiphase with a metronome using the two hands in alternation.…”
Section: Feeling In Controlmentioning
confidence: 99%
“…Coordination is considered to be an effective mechanism to evolve the complex system [4,5]. It is firstly proposed by Hermann Haken in the 70s of the 20 th century.…”
Section: B Coordinationmentioning
confidence: 99%